2022
DOI: 10.46793/match.88-3.561a
|View full text |Cite
|
Sign up to set email alerts
|

The Minimum Sombor Index for Unicyclic Graphs with Fixed Diameter

Abstract: As a novel member of the class of vertex-degree-based topological indices, the so-called Sombor index was recently introduced by Gutman on the chemical graphs. In this paper, we present the minimum Sombor index for unicyclic graphs with the diameter D>_2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Te graphs possessing the least and largest values of the SO index among all unicyclic graphs with a fxed order were found independently in [10,11]. Liu [12] (respectively, Alidadi et al [13]) reported the graphs attained the highest value (respectively, least value) of the SO index among all unicyclic graphs with a fxed diameter and order. Te graphs attaining the minimum (respectively, maximum) SO index over the class of all unicyclic graphs with a fxed maximum degree (respectively, matching number) and order were characterized in [14] (respectively, in [15]).…”
Section: Introductionmentioning
confidence: 98%
“…Te graphs possessing the least and largest values of the SO index among all unicyclic graphs with a fxed order were found independently in [10,11]. Liu [12] (respectively, Alidadi et al [13]) reported the graphs attained the highest value (respectively, least value) of the SO index among all unicyclic graphs with a fxed diameter and order. Te graphs attaining the minimum (respectively, maximum) SO index over the class of all unicyclic graphs with a fxed maximum degree (respectively, matching number) and order were characterized in [14] (respectively, in [15]).…”
Section: Introductionmentioning
confidence: 98%
“…where d x is the degree of vertex x. Some results for the mentioned indices can be found in [1], [3], [6], [7], [10], [12], [13], [14] and the references therein.…”
Section: Introductionmentioning
confidence: 99%
“…The icosahedral fullerene graphs, introduced by Andova and Škrekovski in 2013 [1], are the graphs such that the centers of the pentagonal faces form an icosahedron. The full icosahedral symmetry fullerene graphs G i,0 , where i ≥ 1, is a perfectly symmetric icosahedral fullerene graph such that each pentagonal face equidist exactly i units to other 5 pentagonal faces.…”
Section: Introductionmentioning
confidence: 99%